2017
DOI: 10.1177/1055665617730361
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Otitis Media With Effusion in Thai Children With Cleft Palate

Abstract: Otitis media with effusion was common in Thai children with cleft palate. Surveillance of middle ear effusion and ventilation tube insertion contributed to a favorable hearing outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…5 In fact, more than 80% of patients with cleft deformity show pathologies of the middle ear in the first 2 years of their lives. [6][7][8][9] Middle ear effusion results in reduced sound perception and adversely influences speech and language development. 10 The first 12 months of life are particularly important for language acquisition and processing.…”
Section: Introductionmentioning
confidence: 99%
“…5 In fact, more than 80% of patients with cleft deformity show pathologies of the middle ear in the first 2 years of their lives. [6][7][8][9] Middle ear effusion results in reduced sound perception and adversely influences speech and language development. 10 The first 12 months of life are particularly important for language acquisition and processing.…”
Section: Introductionmentioning
confidence: 99%
“…12 Hearing loss from OME may add more severity to any speech defect that already exists from cleft palate. In our previous study, 13 we found that the cumulative incidence of OME in children with cleft palate was 53.7% at 12 months of age and 81.1% when the children reached 24 months old. Chronic middle Original Article SMJ ear effusion and frequent recurrences are characteristic of OME in children with cleft palate.…”
Section: Discussionmentioning
confidence: 77%
“…In our hospital, the prevalence of OME was reported by Ungkanont et al to be around 50%-80%. 33 They also found a significant improvement in the audiograms after palatoplasty. In this series, we found 75% of patients had OME.…”
Section: Discussionmentioning
confidence: 91%